PENGARUH TERAPI SURAH AN-NISA : 59 UNTUK MENINGKATKAN KEDISIPLINAN SISWA MELALUI BIMBINGAN KELOMPOK DI SMAN 15 PEKANBARU - Pipit Nopriani; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract:This study aims to examine the effect of sura nisa surah therapy: 59 to improve student discipline at SMAN 15 Pekanbaru. This type of research is a quantitative study with an experimental method using a One-Group Pretest-Posttest Design research design. The measuring instrument used in this study was the scale of student discipline measurements consisting of 40 items before validation, and after validation obtained 25 items with a valid validity of 0.5613 and a reliability of 0.868. The subjects of this study were 7 students who were identified as having low levels of discipline. Data analysis technique used is non-parametric statistical techniques using Wilcoxon test. The results of the study proved the research hypothesis was accepted. For this reason, it can be concluded that there are differences in student disciplinary scores before and after treatment in the form of sura anisa nisa therapy: 59. From the Spearman rank test results obtained the correlation r = 0.716 while coefficient determinant r2 is 0.512. Thus there is the influence of sura anisa nisa therapy: 59 on student discipline by 51% at SMAN 15 Pekanbaru.Key Words: Surah An-Nisa Therapy: 59, Student Discipline, Group Guidance